THE DEVELOPMENT MODEL OF CREATIVE INDUSTRY INNOVATION CAPABILITIES: THE LITERATURE STUDY - Nikolas Fajar Wuryaningrat; Paulus Kindangen; Greis Sendouw; Bode Lumanouw (Journal of International Conference Proceedings (JICP), 2018)
The sustainable competitive advantage of small and medium enterprises (SMEs) in creative industry could be demonstrated through the innovation capabilities. In knowledge management literature, knowledge sharing is the key effort to develop innovation capabilities. There are two contrasting theories of Knowledge sharing, Szulanski's (1996) theory assumes a knowledge sharing process is 'sticky' and ambiguous, while Nelson (1981) considered knowledge sharing to be an automatic process in an organization. This study arguing, employee fit will make impact on trust is a relatively new idea to bridging the two contrasting theories. Through the study, it was found that in order to develop the innovation capabilities of SMEs in the creative industry, knowledge sharing is needed, where trust is a crucial factor in knowledge sharing literature. However, building trust is not a simple matter, it assumed that the theory of employee fit (person job fit and person organization fit) can be useful to build trust in the organization. The results of this literature study can be concluded that the model of SMEs in creative industry innovation capabilities followed by employees fit with the competencies required by the company and the individuals value with corporate values. From employee fit, it were expected to facilitate trust in the company which in turn can be useful for knowledge sharing to develop innovation capabilities. Keyword : knowledge sharing, innovation capabilities, person job fit, person organization fit, trust